RME-based local instructional theory for translation and reflection using of South Sumatra dance context - Rawani, Dewi; Putri, Ratu Ilma Indra; Zulkardi; Susanti, Ely (Journal on Mathematics Education, 2023)
A learning trajectory as a sequence of mathematical activities that could facilitate the growth of students’ understanding of learning goals. This research aimed to produce an instructional sequence to learn the concepts of translation and reflection and to investigate how students develop their understanding informally using a South Sumatra dance context. The research employed the design research method, which consisted of three stages: preliminary design, design experiment (pilot experiment and teaching experiment), and retrospective analysis. This research involved six students who have the high, medium, low capability at the first cycle and 32 students ninth graders at the second cycle at Junior High School 1 Palembang. Data from observations, tests, interviews, and documentation were analyzed descriptively. The tests used were aimed to determine the improvement made by the students; while the classroom observations, interviews, and documentations were used to develop the local instructional theory. This study produced a learning trajectory with three activities include: the students watched a dance video to describe the dancer’s’ positions in relation to floor tiles; the students were asked to determine the starting points of the dancers in Cartesian coordinates to learn concepts; and the students developed a formal concept based on their own knowledge.